Choosing Wisely in the UK: the Academy of Medical Royal Colleges' initiative to reduce the harms of too much medicine. (12th May 2015) - Malhotra, A; Maughan, D; Ansell, J; Lehman, R; Henderson, A; Gray, M; Stephenson, T; Bailey, S
Abstract : A Malhotra and colleagues explain how and why a US initiative to get doctors to stop using interventions with no benefit is being brought to the UK